Noah - Kwapis, Ken (USA: Walt Disner Home Video [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor])
Set sail for comedy with Disney's Noah- the humorous modern-day twist on the biblical story of Noah's ark
n.2 is acquisition for KPI (kelab Pencinta Ilmu)
Executive producer, Karen Tangorra ; editor, Donald Ehlers
Cast: Tony Danza
Keywords: Comedy films; Family in motion pictures